2005
DOI: 10.1038/nrn1725
|View full text |Cite
|
Sign up to set email alerts
|

Storage solutions: treating lysosomal disorders of the brain

Abstract: Many neurodegenerative diseases are characterized by the accumulation of undegradable molecules in cells or at extracellular sites in the brain. One such family of diseases is the lysosomal storage disorders, which result from defects in various aspects of lysosomal function. Until recently, there was little prospect of treating storage diseases involving the CNS. However, recent progress has been made in understanding these conditions and in translating the findings into experimental therapies. We review the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
152
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(157 citation statements)
references
References 143 publications
3
152
0
2
Order By: Relevance
“…24 In agreement with previous reports, the NPC mut/mut sample showed a large accumulation of microglia with the typical amoeboid morphology characteristic of activated cells, whereas only ramified (resting) microglia were seen in NPC WT/WT animals. 4,22,25 However, there was no obvious difference in NPC mut/mut mice with or without expression of the Rab9 transgene in either 7-or 10-week-old animals (data not shown). ii) Weight loss.…”
Section: Resultsmentioning
confidence: 89%
“…24 In agreement with previous reports, the NPC mut/mut sample showed a large accumulation of microglia with the typical amoeboid morphology characteristic of activated cells, whereas only ramified (resting) microglia were seen in NPC WT/WT animals. 4,22,25 However, there was no obvious difference in NPC mut/mut mice with or without expression of the Rab9 transgene in either 7-or 10-week-old animals (data not shown). ii) Weight loss.…”
Section: Resultsmentioning
confidence: 89%
“…Pathophysiologic studies of patients and animal models have identified changes in neuronal connectivity in the cerebral cortex, including degeneration of axons and synapses of inhibitory neurons (axon swelling or 'spheroids'), regrowth of dendrites (ectopic dendrites or meganeurites), and formation of new synapses of pyramidal neurons. [17][18][19][20] Many of these phenomena have been attributed to ganglioside storage, albeit the underlying molecular effectors are still unknown. Neuronal cell death and demyelination occur in some of these LSDs [21][22][23] and are often accompanied by astrogliosis and microgliosis that appear mostly in areas of severe neuronal vacuolation.…”
Section: Metabolism Of Gangliosidesmentioning
confidence: 99%
“…Current treatment modalities for LSDs are bone marrow transplantation together with enzyme replacements. These provide benefit to visceral manifestations but not address the CNS pathologies that are both a common and significant signature for disease [58]. These are limited as therapeutic agents cannot cross the BBB.…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%